The Arctic DP Research Project: Effective Stationkeeping in Ice - Skjetne, Roger; Imsland, Lars Struen; Løset, Sveinung (Modeling, Identification and Control: A Norwegian Research Bulletin, 2014)
Stress on the environment from a potentially growing energy use is set to rise. Without doubt the energy resources in Arctic regions will be developed. An important goal will be to exploit the resources offered by for instance the Barents Sea as a new European energy province, and to do this in accordance with the principles of sustainable development that have successfully been used e.g. in the North Sea. The special edition of MIC on Arctic DP presents a set of articles that summarize to an extent the activities of the research project Arctic DP: Safe and green dynamic positioning operations of offshore vessels in an Arctic environment. This project was awarded in 2010 by the Research Council of Norway (RCN) as a competence-building project (KMB project) to NTNU and its partners Kongsberg Maritime, DNV GL, and Statoil. The objective was to target some of the challenges related to safe Arctic offshore operations by dynamic positioning. In this first article of the Arctic DP special edition we discuss the background for and establishment of the project, its planning and execution, and project closure. An overview is given for the scientific and engineering research performed in the project, with an account of what we have considered as Effective stationkeeping in ice by dynamic positioning. The corresponding research activities conducted under this main theme is summarized. Creative Commons Attribution 3.0 Unported (CC BY 3.0) license